THE EFFECT OF MANAGERIAL OWNERSHIP, DIVIDEND POLICY AND DEBT ON FIRM VALUE: THE INDONESIA STOCK EXCHANGE CASES - Lailah Fujianti; Aulia Keiko Hubbansyah; Safitri Siswono; Lazarus Sinaga (INQUISITIVE : International Journal of Economic, 2020)
This study aims to analyze the impact of managerial ownership, dividend policy and debt on firm value. Using a sample of 15 companies with an observation period of 8 years (2011-2018), this study finds that managerial ownership and debt policy have a negative effect on firm value. Meanwhile, dividend policy has a positive effect on firm value. This study stresses that the objective of the managerial ownership program to reduce the potential for agency conflicts and increase firm value has not been optimal. This, based on the findings in this study, is caused by the relatively small portion of managerial ownership in the sample companies, which is only about 5 percent of the total share ownership.